Perpustakaan Perguruan Tinggi dan Plagiarisme - Anita Anita; Luki Wijayanti (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Technological developments in the digital era have caused openness to various information to be more easily accessed and used negatively. This can open up opportunities for education actors to commit plagiarism. Overcoming and preventing plagiarism in higher education is not only the responsibility of higher education leaders, but also the responsibility of the academic community, including the library. Libraries cannot remain silent with issues related to plagiarism in the university environment. Libraries have a moral responsibility in fighting plagiarism and this is where libraries are challenged to be able to work together with the parent institution to make various efforts to overcome and prevent the practice of plagiarism. This study aims to find out how the policies taken by universities in preventing plagiarism and what efforts can be made by university libraries in their contribution to tackling and preventing plagiarism. This study uses a Systematic Literature Review (SLR) approach. From the results of the study, researchers found various policy ideas carried out by universities in preventing plagiarism and various efforts that university libraries could do in preventing plagiarism.